2020
DOI: 10.1038/s41366-020-0610-y
|View full text |Cite
|
Sign up to set email alerts
|

Fetal macrosomia in a Hispanic/Latinx predominant cohort and altered expressions of genes related to placental lipid transport and metabolism

Abstract: Fetal overgrowth, termed fetal macrosomia when birth weight is greater than 4000 grams, is the major concern in the treatment of gestational diabetes mellitus (GDM). However, to date, the underlying mechanisms of fetal macrosomia have not been understood completely. Placental lipid metabolism is emerging as a critical player in fetal growth. In this study, we hypothesized that fatty acid transport and metabolism in the placental tissue was impaired in GDM women, dependent on fetal sex. To test this hypothesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Among others, intensified placental transport of glucose and amino acids to the fetus and its higher mass were found in women and animals using a diet that favors obesity [ 45 , 49 , 50 , 51 ]. Changed transport of lipids in the placenta was found in obese women with GDM which can contribute to fetus overgrowth [ 52 ]. In the literature, the need for effective control of glycaemia is also emphasized during pregnancy in women without GDM, as a factor which is connected with macrosomia risk [ 7 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among others, intensified placental transport of glucose and amino acids to the fetus and its higher mass were found in women and animals using a diet that favors obesity [ 45 , 49 , 50 , 51 ]. Changed transport of lipids in the placenta was found in obese women with GDM which can contribute to fetus overgrowth [ 52 ]. In the literature, the need for effective control of glycaemia is also emphasized during pregnancy in women without GDM, as a factor which is connected with macrosomia risk [ 7 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lipid-transport related genes are selectively activated in macrosomia placenta, and the lipid transport function may be enhanced, which suggests that altered placental lipid transport may contribute to fetal overgrowth in healthy women without GDM. It has been reported that the expression of these genes is also increased in the placenta of GDM women (28) and the changes of placental lipid transport may be related to fetal overgrowth in obese women with GDM [29]. And a previous study found that the expression of FATP6 and FAT/CD36 is increased in placental microvillous plasma membrane of individuals with intrauterine growth restriction (IUGR) [30].…”
Section: Discussionmentioning
confidence: 99%
“…It undoubtedly exacerbated the fetal overgrowth, thereby linking the formation of macrosomia and LGA. Second, the increase of placental lipid metabolism may act a regulatory role in the fat accumulation of the fetus in turn forming macrosomia (50,51). Third, epigenetic regulation occurs via numbers of procedures including DNA methylation (DNAm) and so on.…”
Section: Adverse Infant Birth Weightmentioning
confidence: 99%